Comprasion of ICare Rebound Tonometer and Goldmann Applanation Tonometer in High Myopia. (14th October 2014) - Cagatay, Halil Huseyin; Ekinci, Metin; Yazar, Zeliha; Gokce, Gokcen; Ceylan, Erdinc
Abstract : Purpose. To compare intraocular pressure (IOP) measurements with the Goldmann applanation tonometer (GAT) and the ICare rebound tonometer (RBT) in high myopic eyes. Patients and Methods . This randomized prospective study included 40 eyes of 40 patients with high myopia. All patients' central corneal thickness (CCT), anterior chamber depth (ACD), axial length (AXL), keratometry, and refractive measurements were recorded and followed by IOP measurement with RBT and GAT. Results . The average CCT, AXL, and ACD were determined to be 514.65 ± 32   μ m, 27.65 ± 2.22  mm, and 3.25 ± 0.51  mm, respectively. Mean K was 43.27 ± 1.4  D and mean spherical equivalent was - 11.31 ± 4.30  D. The mean IOP values obtained by RBT and GAT were 17.18 ± 3.72  mmHg and 16.48 ± 3.19  mmHg, respectively. The deviations of RBT readings from corrected GAT values were highly correlated with CCT values (r = 0.588, P = 0.0001 ). The mean corrected GAT reading was 17.49 ± 3.01  mmHg. Linear regression analysis showed that a CCT change of 10  μ m resulted in an RBT reading deviation of 0.57 mmHg. The Bland-Altman scatter-plot and McNemar test showed a clinically good level of agreement between the two tonometers. Conclusion . This study found a good agreement level between the two tonometers in high myopic patients and that RBT measurements are influenced by CCT variations.